2018
DOI: 10.1007/s40430-018-1311-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of three lobe hydrodynamic journal bearing using CFD–FSI technique based on response surface evaluation

Abstract: This work is continuation of the earlier work published on an analysis of plain cylindrical journal bearing using CFD-FSI technique. Here, the technique is applied to analyse three lobe journal bearing. The numerical simulations were carried out using ANSYS WorkbenchÒ software. The hydrodynamic pressures were computed using computational fluid dynamics (CFD), and structural deformations were estimated using structural module. The fluid pressure forces and displacements were transferred via inbuilt transfer int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…They concluded that the multiphase flow analysis along with cavitation and FSI is significant for the journal bearings operating at high speeds. In the other research, Dhande et al [21] simulated lobe hydrodynamic journal bearings using two-way FSI based on the response surface optimization. The main objective was to study the effects of eccentricity ratio and rotational speeds on the pressure distribution.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the multiphase flow analysis along with cavitation and FSI is significant for the journal bearings operating at high speeds. In the other research, Dhande et al [21] simulated lobe hydrodynamic journal bearings using two-way FSI based on the response surface optimization. The main objective was to study the effects of eccentricity ratio and rotational speeds on the pressure distribution.…”
Section: Introductionmentioning
confidence: 99%
“…• Assumption of an initial value of φ and g in the active region for the first iteration. • Obtaining the film thickness at each node from Equation (7).…”
Section: Computational Algorithmmentioning
confidence: 99%
“…The efficiency of journal bearing surface texturing was determined by a fluid flow model in a single micro-scale irregularity unit cell implemented by de Kraker et al [6] using Navier-Stokes equations rather than Reynolds equation. Dhande et al CFD-FSI technique presented in [7] was used by Meng et al [8] to investigate the influence of a complex dimple on the tribological behaviour of the journal bearing. It was found that depending on the geometry and size of the compound dimples, as well as the bearing's operating parameters, a higher load might be followed by a lower coefficient of friction.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that including the effect of bearing microroughness enhanced the load-carrying capacity of such a bearing. Dhande et al [10] used the CFD approach to analyze the elastohydrodynamic lubrication of three-lobe journal bearing. The obtained results were validated against the experimental results and they were found to be in the expected range.…”
Section: Introductionmentioning
confidence: 99%